The practice of supply chain management where theory and application converge - Harrison, Terry P. (International series in operations research & management science, 2005)
For over a decade, there has been an increasing interest in the use of supply chain methods to improve performance across the entire business enterprise. Numerous industries have recognized the importance of efficient supply chain integration, and, as a result, supply chain management has become a standard part of business practice. The focus of the book is on supply chain practice, but supply chain practice that has been heavily influenced by supply chain research. It is this synergy between research and practice that continues to simulate new directions for research.